ANALYSIS OF THE LANGUAGE USED BY INTER-CASTE MARRIAGE (NYEROD) OF BALINESE WOMEN IN COMMUNICATING WITH THEIR FAMILY - Dewa Ayu Made Juli Astari; Ni Nyoman Padmadewi; Ni Luh Putu Eka Sulistia Dewi (UIBU, 2023)
This study aims to analyze the language used by Balinese women who have inter-caste marriages (Nyerod) in their communication with their families. A phenomenological technique was applied in this study. Serokadan Susut Bangli is the location of the research. The data was gathered in two ways: through observation and interviews. During observation and interviews, the researcher took notes. The objects of study were (1) the language used by men's families to communicate with Balinese women; and (2) the language used by Balinese women to communicate with their families before and after marriage. Three Balinese women were the subjects. The data was examined following the procedure described by Miles and Huberman, which included reducing the data, interpreting the data, and drawing a conclusion. The result showed differences in the language used, where the men's families use low-level Balinese or Basa Bali Biasa to communicate with Balinese women of inter-caste marriages (Nyerod). The language used by Balinese women to communicate with their families before marriage was Basa Bali Madia, and after marriage, they used the polite Balinese language or Basa Bali Alus.